MEKANISME EUFEMISME DAN SENSORISASI: KEKERASAN SIMBOLIK DALAM TUTURAN DOSEN - Galieh Damayanti; Trisna Andarwulan; Aswadi Aswadi (Universitas Negeri Makassar, 2019)
Abstract: Symbolic Violence Representation in the Mechanism of Euphemism and Sensori-zation of Lecturer Speech. This study aims to describe the representation of symbolic violence in the mechanism of euphemism and censorship of lecturers' speeches to students in the class. This study uses a qualitative approach with a type of case study research. Data in the form of sentences in lecturer speech to students. Data collection techniques used are observation, recording, and recording. Bourdieu's social class theory which was constructed in the mechanism of euphemism and censorship became the basis for studying this research data. Symbolic violence is represented in the mechanism of euphemism and the censorship mechanism. The results of the study show that symbolic violence through lecturer speech inspired by institutional authority shapes the behaviors, thoughts, and beliefs that can be accepted in certain social spaces. This is done on the basis of